SIGWEB OBYEK WISATA DI KABUPATEN SOLOK - Silvi Widya Rahmi; Arie Yulfa (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to determine: 1) To map the distribution of tourism objects in Solok Regency, 2) To build SIGWeb as an information technology media for tourism destinations in Solok Regency. This type of research is classified as quantitative descriptive using the System Development Life Cycle (SDLC) method with the Waterfall model and purposive sampling technique. The population of this research is the geography students from 2016, 2017, 2018, totaling 365 students and the sample has been calculated using the Slovin formula to be 190 students. Collecting data using observation, interviews and questionnaires. Data analysis used is 1) Nearest Neighbors Analysis (NNA), 2) Building SIGWeb using the waterfall method and assessment with a Likert scale. The results of this study indicate, to overcome the lack of information on tourist destinations and the absence of spatial based information technology media in Solok Regency. Therefore, information technology media is needed, namely SIGWeb Tourism Object, and after conducting a review, making SIGWeb, and assessing through a questionnaire, it is stated that the SIGWeb built is very helpful in providing the information needed.